Patient Positioning and Skin Sequelae: Ischemic Epidermal Necrosis from Tight Padding During Cardiac Surgery. Issue 10 (15th May 2016) - Sadeghpour, Mona; Au, Jeremiah; Ho, Jonhan; Hyman, Jaime; Patton, Timothy
Abstract : Careful positioning and padding of pressure points during surgery are recommended to prevent pressure ulcers, vascular injury, and nerve damage in an immobilized patient. However, overpadding may have unintended consequences. We report a case of ischemia-induced full-thickness epidermal necrosis secondary to tight foam padding during a cardiac surgery.